Assessing Redistribution in the Uruguayan Social Security System - Forteza, Alvaro; Mussio, Irene (Journal of Income Distribution®, 2013)
We assess redistribution in the main Uruguayan pension and unemployment insurance programs on a lifetime basis. Using administrative records from Social Security, we simulate lifetime declared labor income and flows of contributions and benefits to affiliates to the programs. Expected present values of income and net flows are also computed. Equipped with these estimations, we construct standard measures of distribution and redistribution of lifetime labor income through the Social Security system. Our findings suggest that these programs reduce income inequality. In particular, Social Security reduces the Gini coefficient of expected lifetime formal labor income by almost 2 percentage points.